Unemployment and the wellbeing of children aged 5-10 years - Edwards, Ben; Gray, Matthew; Taylor, Matthew (My University, 2011)
The extent to which an increase in the unemployment rate has an effect on children's wellbeing is not well understood. This article provides estimates of the potential impact of an increase in the unemployment rate on behavioural and emotional outcomes for New South Wales (NSW) children aged four to five to eight to nine years. It also examines the extent to which the negative impacts are concentrated within particular geographic areas. It is estimated that an increase in the unemployment rate leads to an increase in the number of children with behavioural or emotional problems. This finding underscores the importance of having macro-economic policies that limit the increases in the rate of joblessness during economic downturns, particularly policies aimed at reducing the rate of family joblessness.
Australian Journal of Labour Economics
Keywords: Employment -- Unemployment; Child Development; Children -- Outcomes; Childhood and child development; Labour market; Children; Employment; Child Development; Outcomes; Unemployment; Employment and unemployment; Childhood and child development